On-Farm Assessment of AquaSpy Soil Moisture Sensors for Irrigation Scheduling - P. Rossini; A. Patrignani (Kansas Agricultural Experiment Station Research Reports, 2021)
The aim of this study was to compare a commercially-available radio-frequency (RF) spectroscopy soil moisture sensor with an array of calibrated research-grade soil water reflectometers in a no-till irrigated corn field from June to September 2020. The RF probe consisted of 12 sensors spaced at 4-inch intervals across 48 inches in length, while the array of soil water reflectometers consisted of four sensors deployed along the soil profile at 4, 12, 20, and 28 in. depth. Soil moisture sensors were installed at approximately 30-ft apart in two different regions within the same field characterized by contrasting soil textural classes. Hourly soil moisture and soil temperature were collected by both sensors and compared across the study period. The RF probe closely followed the soil moisture dynamics captured by the research-grade sensors. Preliminary results reveal that the tested RF sensor is useful for irrigation scheduling based on relative soil moisture values. Field-specific calibrations are required to translate the relative soil moisture measurements of the RF sensor into soil water storage in terms of volumetric water content or inches of water in the soil profile.
Keywords: Soil moisture sensor; irrigation scheduling; on-farm research